2016
DOI: 10.1098/rstb.2015.0446
|View full text |Cite
|
Sign up to set email alerts
|

Energy and time determine scaling in biological and computer designs

Abstract: One contribution of 13 to a theme issue 'The major synthetic evolutionary transitions'. Metabolic rate in animals and power consumption in computers are analogous quantities that scale similarly with size. We analyse vascular systems of mammals and on-chip networks of microprocessors, where natural selection and human engineering, respectively, have produced systems that minimize both energy dissipation and delivery times. Using a simple network model that simultaneously minimizes energy and time, our analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Conversely, healthy host-cell dynamics can be represented through a transient stationary state of relevant stocks (i.e., Q1, Q2A and Q2B). The use of energy as key parameter in modelling the virus-host co-evolution, at the level of the single cell, complies with the medical literature evidence, showing the relevance of energy as a descriptor of biosystems in medicine [68][69][70][71] .…”
Section: Discussionsupporting
confidence: 56%
“…Conversely, healthy host-cell dynamics can be represented through a transient stationary state of relevant stocks (i.e., Q1, Q2A and Q2B). The use of energy as key parameter in modelling the virus-host co-evolution, at the level of the single cell, complies with the medical literature evidence, showing the relevance of energy as a descriptor of biosystems in medicine [68][69][70][71] .…”
Section: Discussionsupporting
confidence: 56%
“…This property allows transfer of information among entirely different material or energetic systems, allowing the structure and materials of information processing systems to be plastic without necessarily compromising information flow. Information processing systems are typically characterized by indeterminacy in channels, and plasticity in the particular flows of information confer stability on the processing network (Patten and Odum, 1981;Flack et al, 2006;Moses et al, 2016), much as MacArthur showed in his idealized food web (MacArthur, 1955). Information processing systems can adapt to changing conditions, often reversing structural patterns in ecological networks (MacArthur, 1955;Ulanowicz, 2001;Flack et al, 2006;Ulanowicz et al, 2009;Valdovinos et al, 2016).…”
Section: How Is Information a Dynamic Part Of Living Systems?mentioning
confidence: 99%
“…Our work studies a specific example of this morphospace as instantiated by travel paths in cities. Moses et al [33] study trade-offs between minimizing delivery time and energy dissipation required for delivery of a resource, and they find scaling principles between the two in vascular networks and computer chip designs. Thus, while the idea of studying network design trade-offs across engineered and biological contexts is not new, our study instantiates these ideas in a specific domain of single-source transport systems.…”
Section: Additional Work In Pareto Optimality Of Complex Networkmentioning
confidence: 99%